Obciążenie podatkiem dochodowym umów leasingowych w Niemczech i Wielkiej Brytanii - Rękas, Magdalena (Income tax charges in Great Britain and Germany, 2006)
Leasing is one ofthe forms of investment financing, which has not been sufficiently appreciated in Poland. The opportunity to make use of tax benefits is one ofthe factors that encourage one to use leasing. The aim of the article is to present lax regulations concerning leasing contracts in the scope of income tax applied in Great Britain and Germany. The level of investment financing through leasing amounted in 2004 in Great Britain to 24.5 %, in Germany to 17.1%, while in Poland it only exceeded 10%. The analysis was also performed to show whether there are such solutions in the presented regulations, the application of which could stimulate leasing use in Poland and encourage foreign investors to conclude leasing contracts with Polish leasing companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 230-241